Idiopathic pulmonary hemorrhage: morphology and differential diagnosis. Case report - Cambruzzi,Eduardo (2013)
Idiopathic pulmonary hemorrhage (IPH) is a rare cause of alveolar hemorrhage (AH) with unknown etiology that primarily affects children. The process has a variable clinical progression, and its diagnosis is established after excluding all causes of AH. Herein, the authors report a case of IPH in an adult male patient referring cough and hemoptysis. The conventional radiography computed tomography imaging identified zones of consolidation and areas of ground-glass attenuation in the lower lobes and lingula. Forced spirometry, bronchoscopy, and laboratorial tests yielded normal results. Several alveolar hemosiderin-laden macrophages were identified on bronchoalveolar lavage and lung biopsy. Thus, the histopathological findings associated with clinical data were compatible with IPH.